2018
DOI: 10.4236/me.2018.912126
|View full text |Cite
|
Sign up to set email alerts
|

Debt, Corruption and Investment in East Africa: A Panel ARDL Analysis

Abstract: We set out to investigate the relationship between public debt and private investment using a panel of four countries in East Africa for the period 1992-2015. The results from the Autoregressive Distributed Lag Models show that Public Debt (PD) crowds out both Private Domestic Investment (PDI) and Foreign Direct Investment (FDI) in the long run, although the magnitude of the impact is greater for the former category. We fail to find evidence of any short run significant relationship in either case. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our results show that increasing domestic public debt and debt service costs in South Africa have had a negative effect on private capital formation during the recent years. These findings support the crowding-out proposition and previous findings in papers such as Aswata et al (2018). However, external public debt is found to crowd-in private investment.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results show that increasing domestic public debt and debt service costs in South Africa have had a negative effect on private capital formation during the recent years. These findings support the crowding-out proposition and previous findings in papers such as Aswata et al (2018). However, external public debt is found to crowd-in private investment.…”
Section: Introductionsupporting
confidence: 91%
“…In sub-Saharan Africa (SSA), this result has been established for Nigeria (Akomolafe et al, 2015) and the SSA region (Ghura and Goodwin, 2000). Aswata et al (2018) further explore the relationship between public debt and both domestic private and foreign direct investment in East Africa. Whilst the crowding-out effect is observed in their results, an interesting finding is that the impact decreases when corruption is controlled for.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Aschauer [7] found that public investment crowds-in private investment. Similarly, two other studies also support the existence of the crowding-in effect public on private investment [3] and [5]. Authors [28] found a greater crowding-in effect in developing rather than developed countries by public investment.…”
Section: Literature Reviewmentioning
confidence: 63%
“…The ARDL model is used in the paper because it is applied if all the time series variables are either I(0) or I(1) and/or if they are a combination of I(0) and I(1) but it cannot be used if one of the time series variables is I(2) (Pesaran et al, 2001). In addition, the method produces unbiased estimates even in the presence of endogenous covariates, applies to small sizes like for our paper, and estimates the short-run and long-run dynamic relationship among macroeconomic variables (Shaari et al, 2022 andAswata et al, 2018). The estimated ARDL model is specified as presented in Equation ( 2).…”
Section: Literature Reviewmentioning
confidence: 93%